Postharvest Technology : Cereals, Fruits, Vegetables, Tea, and Spices - Amalendu Chakraverty (MARCEL DEKKER, 2003)
The need to increase food production to meet the requirements of a rapidly growing world population is widely recognized. Cereals, pulses, fruits, and vegetables are the important food crops in the world as these are the bulk sources of calories, proteins, and nutrients, and spices and plantation crops play an important role in the economies of many countries. To supply an adequate quantity of grains and other food to the expanding world population is a challenge to mankind. Rice and wheat have an added importance in national and international trade with political and social implications. The supply of grains and other food crops can be augmented by increasing production as well as by reducing postharvest losses. The production of food has increased significantly during the last few decades due to successful research and development efforts in both areas. The use of recently developed high-yielding crops has created a high yield potential when it is supplemented with suitable application of fertilizer and modern management practice. The term ‘‘green revolution’’ is used to reveal the impact of highyielding cultivars on the world of agriculture.